The Voices of Young Carers in Policy and Practice - Phelps, Daniel (Social Inclusion, 2017)
This article presents examples from England of the participation of children with caring responsibilities (young carers) in policy and practice at both local and national levels. The ‘voices' of young carers themselves have become more prominent at many levels and in diverse contexts such as through local young carers’ fora and through dialogue with decision makers, including social care commissioners and Members of Parliament. This participation has for a number of years in England, been strongly advocated for and facilitated by voluntary sector services in particular. Drawing on a number of practice examples, the article will highlight a range of young carers' participatory activity and the extent to which this is woven into policy development and practice. It will consider the processes and protocols of recruitment and safeguarding and the outcomes of young carers' participation, including the influence of their ‘voices’ in bringing about real change and the impacts on themselves as individuals. Consideration will be given as to whether the voices of young carers has been truly representative of children and young people with caring responsibilities and where particular attention may need to be focused when listening to their voices. The potential risks of young carers' participation at a practical level will be explored as well as the barriers to participation for young carers and approaches for enhancing their participation.